Estudo da atividade antineoplásica do complexo rutênio (II) com ligante 2-mercaptotiazolina - Melo, Matheus Reis Santos de (2022)
Melanoma is the least affected type of skin cancer in the world, however, it is the most aggressive and lethal due to its characteristics such as high metastatic potential and low response rate to existing treatment modalities. Thus, new drug prototypes are being developed to solve the problem of treating patients with melanomas. Among the prototypes, metallopharmaceuticals such as ruthenium have emerged as promising alternatives due to their selective antitumor characteristics and low systemic toxicity. In this context, the present study evaluated the complex effect of ruthenium [Ru(mtz)(dppe)2]PF6 (RuMTZ) on human (A-375) and murine (B16-F10) melanoma tumor cell lines, considering different approaches. The results demonstrate that RuMTZ has cytotoxic activity, with IC50 values ranging from 2.1 to 19.6 µM in the XTT colorimetric assay and from 0.3 to 1.28 µM in the clonogenic efficiency assay. RuMTZ also induced changes in cell morphology and inhibited cell migration by 35.17% and 43.87%, respectively, for A-375 and B16-F10. Furthermore, an increase in cell populations with fragmented DNA in the sub-G0 phase was observed in both melanoma cell lines and an increase in the level of apoptosis in A-375. Molecular assays showed the absence of cleaved capase-3 for both cell lines. The data obtained indicate that RuMTZ has promising antitumor and anti-metastatic activity against melanoma. Keywords: Thiazoline, melanoma, antitumor activity, metallodrug